Mechanical properties assessment of a 3D printed composite under torsional and perpendicular stress - Lovo, João Fiore Parreira (2022)
Purpose: This paper aims to evaluate the resin infiltration influence on the mechanical properties of components 3D printed by the material extrusion-based additive manufacturing (AM), also known as fused deposition modeling and commonly uses the acrylonitrile butadiene styrene (ABS) as depositing material. Improvements in their mechanical properties are desirable due failure resulting from the extrusion process. In this way, resin infiltration is considered a candidate solution to enhance 3D printed components’ strength. Design/methodology/approach: The mechanical properties of AM samples produced with and without the resin infiltration were assessed under torsion, tensile and flexural stresses. Torsional tests are rarely found applied for this case, an alternative torsion test developed by one of the authors was used. The torsion modulus (G) is obtained without the Poisson’s ratio, which is usually unknown for recently made composites. Scanning electron microscopy was also done to verify the resin infiltration on the samples. Findings: Results demonstrated that the resin infiltration on ABS can improve the mechanical properties of samples compared to non-infiltrated. The tensile and bending strength increased more than 6%. Both Young’s and torsion modulus also presented a significant increase. The samples did not present any considerable change in their weight property. Originality/value: This paper discusses on resin infiltration on print ABS, as to produce a composite material, enhancing ABS properties without gaining weight. This paper also used the torsion modulus instead of the common approach of bringing only tensile and flexure strength.